Soil structure is an important omission in Earth System Models - Simone Fatichi (Nature Portfolio, 2020)
The effect of soil structure is not included in most Earth System Models. The authors here introduce and evaluate the consequences at local and global scale of modifying hydraulic properties of soils in response to biological activity—a process significantly changing soil structure.